2016
DOI: 10.22601/pet.2016.01.06
|View full text |Cite
|
Sign up to set email alerts
|

English-Estonian code-copying in Estonian blogs

Abstract: Abstract. Th e article discusses English-language impact on Estonian in online blogs. Th e data comprise blog entries from 15 Estonian fashion, beauty and lifestyle blogs from 2012 to February 2016. Th e corpus consists of 283 post entries (141,480 words (tokens)). Th e research showed that there are far fewer selective copies than global copies, probably because selective copies appear at more advanced stages of acquisition. Global copies are usually copied due to semantic specifi city, for example fashion le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Unfortunately, we lack objective data on the child-directed speech heard by the children in this study, and more generally, we lack comparable spoken data from adults bilingual in English and Estonian. Recent research has found some variability in the use of English and Estonian in computer-mediated communication (on Facebook, Igav 2013; in blogs, Kask 2016). Most of the studies to date, however, involve native Estonian speakers who make liberal use of L2 English in their writing.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, we lack objective data on the child-directed speech heard by the children in this study, and more generally, we lack comparable spoken data from adults bilingual in English and Estonian. Recent research has found some variability in the use of English and Estonian in computer-mediated communication (on Facebook, Igav 2013; in blogs, Kask 2016). Most of the studies to date, however, involve native Estonian speakers who make liberal use of L2 English in their writing.…”
Section: Methodsmentioning
confidence: 99%
“…Studies about English-Estonian language contact by Igav (2013), Roosileht (2013) and Vaba (2010) confirm that English adjectives are often used to signal attitudes, they convey strong emotions and are prominent on the pragmatic level. They are also more colourful and add expressiveness to the text (Kask 2016). For example, adjectives like badass and crappy are both colloquial adjectives, that convey strong emotions and may be a part of the blogger's/vlogger's personal style.…”
Section: Sociolinguistic Background Of Estoniamentioning
confidence: 99%
“…According to Verschik (2019), monological asynchronous genres (like blogs and vlogs) provide a window into these aspects in individual language use and multilingual repertoire. The data for this study comes from Estonian fashion and lifestyle blogs and vlogs, which have proved to be a setting with much English-Estonian language contact (Kask 2016, Ratt 2017, Roosileht 2013, and Verschik and Kask 2019. This study is qualitative.…”
Section: Introductionmentioning
confidence: 99%